2016
DOI: 10.1371/journal.pone.0161259
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Short-Term Traffic Flow Prediction Model Based on Singular Spectrum Analysis and Kernel Extreme Learning Machine

Abstract: Short-term traffic flow prediction is one of the most important issues in the field of intelligent transport system (ITS). Because of the uncertainty and nonlinearity, short-term traffic flow prediction is a challenging task. In order to improve the accuracy of short-time traffic flow prediction, a hybrid model (SSA-KELM) is proposed based on singular spectrum analysis (SSA) and kernel extreme learning machine (KELM). SSA is used to filter out the noise of traffic flow time series. Then, the filtered traffic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 61 publications
0
27
0
Order By: Relevance
“…Traffic analysts have utilized the spatial dependency of road segments to solve three typical problems in a traffic network: (1) short-term traffic forecasting [1, 2, 5, 6], (2) reliable path problem [7], and (3) missing data estimation [8]. …”
Section: Introductionmentioning
confidence: 99%
“…Traffic analysts have utilized the spatial dependency of road segments to solve three typical problems in a traffic network: (1) short-term traffic forecasting [1, 2, 5, 6], (2) reliable path problem [7], and (3) missing data estimation [8]. …”
Section: Introductionmentioning
confidence: 99%
“…Amongst other dimension reduction methods, we note applications of PCA based on singular-value decomposition [74,[79][80][81], non-negative matrix factorisation [82,83], local shrunk discriminant analysis [84], and singular spectrum analysis [79,85,86].…”
Section: Class 5: Dimension Reduction Methodsmentioning
confidence: 99%
“…Zhang et al [26] found that ELMs with heterogeneous data exhibit improvements over linear models in terms of both the level and directional accuracy when handling traffic flow time-series data. Shang et al [27] proposed a shortterm traffic flow prediction model called SSA-KELM (singular spectrum analysis kernel ELM) to reduce the influences of uncertainty and nonlinearity on the expressway system.…”
Section: Introductionmentioning
confidence: 99%